Negative electrode graphite material, graphite negative electrode and production method thereof

By coating the surface of graphite particles with carbonized maleic anhydride grafted polyethylene and adding stannous pyrophosphate, the problem of low compatibility of negative graphite materials for electrolytes is solved, and its electrochemical performance and compatibility is significantly improved. It is suitable for high-energy density lithium-ion batteries.

CN119833623AActive Publication Date: 2025-04-15SHENZHEN XINMAO NEW ENERGY TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510307639.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-15
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The existing negative electrode graphite materials have low compatibility with electrolytes, which has affected the electrical performance of lithium-ion batteries and cannot meet the growing demand for use.

Method used

Maleic anhydride grafted polyethylene is used as the shell to coat graphite particles, and carbonize them by heating to form a conductive carbon chain with rich structures, increasing the number of micropores and structural strength of the negative electrode. At the same time, stannous pyrophosphate is added to improve the compatibility and circulation performance of the negative electrode.

Benefits of technology

The compatibility of the negative electrode graphite material with a variety of electrolytes is significantly improved, its conductivity, capacity and circulation performance is enhanced, and it can store lithium ions more effectively and inhibit the growth of lithium dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833623A_ABST
    Figure CN119833623A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrode materials, in particular to a negative electrode graphite material, a graphite negative electrode and a production method thereof. The negative electrode graphite material comprises core-shell particles of which a core layer is coated with a shell layer. And the shell layer is carbonized maleic anhydride grafted polyethylene. The core layer is graphite particles. The maleic anhydride grafted polyethylene has abundant branched chain structures, conductive carbon chains with abundant structures can be formed after carbonization, and the number of micropores in the negative electrode is increased, so that the lithium ion storage capacity of the negative electrode is improved. In aqueous and organic electrolytes, the negative electrode graphite material has good conductivity, large capacity and good cycle performance, and has good compatibility with a variety of electrolytes. The natural graphite is subjected to surface modification, so that the compatibility of a graphite material to an electrolyte is improved, the electrochemical performance of a graphite negative electrode is improved, and the graphite negative electrode is suitable for being used in a high-energy-density lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrode materials, and more specifically, to a negative electrode graphite material, a graphite negative electrode and a production method thereof. Background Art

[0002] Lithium-ion batteries are widely used in electronics, automobiles, energy storage and other fields due to their high energy density, long cycle life and high safety factor. With the continuous development of battery technology, various sub-sectors have higher and higher requirements for the refined application of batteries, especially key indicators such as cycle life, rate and capacity.

[0003] The structural design of today's lithium-ion batteries is becoming more and more compact, and the reserved space is getting smaller and smaller. Limited by the types of existing battery materials, electrolytes containing different additives have appeared on the market to suit different application scenarios. This means that the electrode material must also have better compatibility with the electrolyte in order to improve the performance of the battery. The market share of negative electrode artificial graphite materials is as high as more than 80%, and the requirements for its electrolyte compatibility are more stringent. General negative electrode graphite materials have low compatibility with electrolytes, which greatly affects the electrical performance of the battery and cannot meet the current growing demand for use. Summary of the invention

[0004] In view of the low compatibility of general negative electrode graphite materials with electrolytes, which greatly affects the electrical performance of the battery and cannot meet the current growing demand for use, the present application proposes a negative electrode graphite material with good electrolyte compatibility, a graphite negative electrode and a production method thereof.

[0005] In a first aspect, the present application proposes a negative electrode graphite material and adopts the following technical solution.

[0006] A negative electrode graphite material comprises core-shell particles in which a shell layer covers a core layer; the shell layer is carbonized maleic anhydride grafted polyethylene; and the core layer is graphite particles.

[0007] By adopting the above technical solution, maleic anhydride grafted polyethylene has a rich branched structure, which can form a rich conductive carbon chain after carbonization, and increase the number of micropores inside the negative electrode, thereby increasing the negative electrode's capacity to store lithium ions. In both aqueous and organic electrolytes, the negative electrode graphite material has good conductivity, large capacity and good cycle performance, and is compatible with a variety of electrolytes.

[0008] As an improvement of the negative electrode graphite material, the mass ratio of the uncarbonized maleic anhydride grafted polyethylene and the graphite particles used to prepare the negative electrode graphite material is (2-10):100.

[0009] By adopting the above technical solution, the negative electrode graphite material prepared by the ratio of maleic anhydride grafted polyethylene and graphite particles has abundant lithium storage space and high structural strength.

[0010] As an improvement of the negative electrode graphite material, the particle size distribution of the graphite particles is: D10 is 5-13 μm, D50 is 13-17 μm, and D90 is 17-35 μm.

[0011] By adopting the above technical solution, the graphite particles with the particle size distribution are used to prepare the negative electrode graphite material, so that there are suitable gaps between the core-shell particles. The prepared negative electrode structure has higher strength and more lithium storage space and better conductivity.

[0012] On the second aspect, the present application also proposes a method for producing negative electrode graphite material, and adopts the following technical solution.

[0013] A method for producing a negative electrode graphite material comprises: mixing and grinding maleic anhydride grafted polyethylene and graphite particles, heating to melt the maleic anhydride and coat the graphite particles, grinding again to disperse the graphite particles coated with the coating material, and then heating to 800-1500°C in an oxygen-free atmosphere and keeping the temperature for 5-20 hours to obtain the negative electrode graphite material.

[0014] By adopting the above technical solution, maleic anhydride grafted polyethylene is coated on the outer surface of graphite particles and carbonized, forming a multi-branched carbon chain conductive structure and pores on the surface of the graphite particles, thereby improving the conductivity and lithium storage performance of the material.

[0015] A preferred embodiment of the production method of the negative electrode graphite material is that the graphite particles are spheroidized graphite obtained by crushing and spheroidizing flake graphite as a raw material.

[0016] By adopting the above technical solution, the spheroidized graphite is advantageously covered completely by the maleic anhydride grafted polyethylene.

[0017] A preferred embodiment of the production method of the negative electrode graphite material is that the sphericity of the spheroidized graphite is ≥80%.

[0018] By adopting the above technical solution, the sphericity of the spheroidized graphite meets the requirement of being completely coated by maleic anhydride grafted polyethylene.

[0019] On the third aspect, the present application also proposes a graphite negative electrode and adopts the following technical solution.

[0020] A graphite negative electrode comprises the above-mentioned negative electrode graphite material, and also comprises stannous pyrophosphate, a conductive agent, a binder and a current collector; the negative electrode graphite material, the stannous pyrophosphate, the conductive agent and the binder are uniformly dispersed with each other in a mass ratio of 10: (0.3-0.5): (0.4-0.8): (1.0-1.5) and are solidified on the current collector.

[0021] By adopting the above technical solution, stannous pyrophosphate is added to the negative electrode, which has stable properties, is insoluble in general electrolytes, and has a certain protective effect on the negative electrode structure. Stannous pyrophosphate has a good dispersion effect in the negative electrode graphite material, conductive agent and binder, so that stannous pyrophosphate dispersed in the negative electrode material can enrich the number of negative electrode micropores and improve the wetting efficiency of the electrolyte on the negative electrode, which is beneficial to the first charge and discharge of the battery. When lithium ions are embedded in the negative electrode surface, a relatively complete SEI film is grown. The complete SEI film can improve the efficiency of lithium ion embedding and detaching from the graphite negative electrode, and also provide a larger storage space for lithium ions to embed into the negative electrode, thereby improving the capacity and cycle performance of the negative electrode. The above makes it possible to add stannous pyrophosphate to the negative electrode to improve the compatibility of the negative electrode with a variety of electrolytes. The growth of lithium dendrites is mainly caused by the fact that lithium ions cannot be efficiently embedded in the negative electrode and grow on the surface of the negative electrode. This solution grows a relatively complete SEI film on the surface of the negative electrode, which improves the efficiency of lithium ion embedding in the negative electrode, and thus can inhibit the growth of lithium dendrites on the surface of the negative electrode.

[0022] In a fourth aspect, the present application also proposes a method for producing a graphite negative electrode, and adopts the following technical solution.

[0023] A method for producing a graphite negative electrode comprises mixing the negative electrode graphite material, stannous pyrophosphate, the conductive agent and the binder with a solvent into a slurry, coating the slurry on the current collector, and drying and curing to obtain the graphite negative electrode.

[0024] By adopting the above technical solution, the method is simple and has wide applicability, and the prepared graphite negative electrode has good compatibility with a variety of electrolytes.

[0025] In summary, the negative electrode graphite material, graphite negative electrode and its production method of the present application have the following beneficial effects: maleic anhydride grafted polyethylene forms a structurally rich conductive carbon chain after carbonization on the surface of graphite particles, and increases the number of micropores inside the negative electrode, thereby increasing the capacity of the negative electrode to store lithium ions, and has good compatibility with a variety of electrolytes. In both aqueous and organic electrolytes, the negative electrode graphite material has good conductivity, large capacity and good cycle performance.

[0026] The addition of stannous pyrophosphate to the negative electrode has a certain protective effect on the negative electrode structure, enriches the number of negative electrode micropores, and improves the capacity and cycle performance of the negative electrode. The addition of stannous pyrophosphate to the negative electrode can improve the compatibility of the negative electrode with a variety of electrolytes and inhibit the growth of lithium dendrites on the surface of the negative electrode.

[0027] The negative electrode graphite material and the production method of the graphite negative electrode of the present application are simple and have wide applicability. Low-cost maleic anhydride grafted polyethylene and stannous pyrophosphate are used to improve the negative electrode performance, and the negative electrode has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 SEM image of the negative electrode graphite material of Example 1.

[0029] Figure 2 SEM image of the negative electrode graphite material of Example 2. DETAILED DESCRIPTION

[0030] The present application is further described below in conjunction with specific examples and drawings, and the advantages and features of the present application will become clearer as the description proceeds. It is particularly noted that if no specific conditions are specified in the following examples, the conventional conditions or the conditions recommended by the manufacturer are followed, and the raw materials used in the following examples can all be sourced from common commercial sources unless otherwise specified.

[0031] Example 1: This example prepares a negative electrode graphite material, and the preparation steps are as follows.

[0032] Natural flake graphite is used as raw material and crushed.

[0033] The crushed graphite is spheroidized by graphite spheroidizing equipment to make the sphericity of the graphite reach 80%, and then screened to control the graphite particle size range of D10>5μm, D50=15±2μm, and D90<40μm.

[0034] Maleic anhydride grafted polyethylene is used as the coating material, and the coating material and spheroidized graphite particles are mixed in a mass ratio of 5:100; then grind for 5 hours to make the coating material fully ground and evenly dispersed with the graphite particles; first heat to 150°C to melt the maleic anhydride grafted polyethylene and coat the surface of the graphite particles; grind again to disperse the graphite particles coated with the coating material; then heat to 1000°C and keep warm for 10 hours under a nitrogen protection atmosphere to achieve carbonization of the coating material on the surface of the graphite particles; finally, the coated graphite is demagnetized and sieved to obtain a negative electrode graphite material, whose microstructure is as follows Figure 1 shown.

[0035] Example 2: This example prepares a negative electrode graphite material, and the preparation steps are as follows.

[0036] Natural flake graphite is used as raw material and crushed.

[0037] The crushed graphite is spheroidized by graphite spheroidizing equipment to make the sphericity of the graphite reach 80%, and then screened to control the graphite particle size range of D10>5μm, D50=15±2μm, and D90<40μm.

[0038] Maleic anhydride grafted polyethylene is used as the coating material, and the coating material and spheroidized graphite particles are mixed in a mass ratio of 2:100; then grind for 5 hours to make the coating material fully ground and evenly dispersed with the graphite particles; first heat to 150°C to melt the maleic anhydride grafted polyethylene and coat the surface of the graphite particles; grind again to disperse the graphite particles coated with the coating material; then heat to 1000°C and keep warm for 10 hours under a nitrogen protective atmosphere to achieve carbonization of the coating material on the surface of the graphite particles; finally, the coated graphite is demagnetized and sieved to obtain a negative electrode graphite material, whose microstructure is as follows Figure 2 shown.

[0039] Example 3: This example prepares a negative electrode graphite material, and the preparation steps are as follows.

[0040] Natural flake graphite is used as raw material and crushed.

[0041] The crushed graphite is spheroidized by graphite spheroidizing equipment to make the sphericity of the graphite reach 80%, and then screened to control the graphite particle size range of D10>5μm, D50=15±2μm, and D90<40μm.

[0042] Maleic anhydride grafted polyethylene is used as a coating material, and the coating material and spheroidized graphite particles are mixed in a mass ratio of 10:100; then ground for 5 hours to make the coating material fully ground and evenly dispersed with the graphite particles; firstly heat to 150°C to melt the maleic anhydride grafted polyethylene and coat the surface of the graphite particles, and grind again to disperse the graphite particles coated with the coating material; then, under a nitrogen protective atmosphere, heat to 1500°C and keep warm for 20 hours to achieve carbonization of the coating material on the surface of the graphite particles; finally, the coated graphite is demagnetized and sieved to obtain a negative electrode graphite material.

[0043] Example 4: This example prepares a graphite negative electrode, and the preparation steps are as follows.

[0044] The negative electrode graphite material prepared in Example 1 was mixed with stannous pyrophosphate, carbon black conductive agent and styrene-butadiene rubber binder in a mass ratio of 10:0.4:0.6:1.2 to form a powder mixture, and N-methylpyrrolidone was used as a solvent. The powder mixture and the solvent were mixed in a ratio of 1g:1mL, stirred into a slurry, and the slurry was coated on a copper foil current collector with a thickness of 10μm. The slurry coating thickness was 200μm, and dried and solidified to obtain a graphite negative electrode.

[0045] Example 5: This example prepares a graphite negative electrode, and the preparation steps are as follows.

[0046] The negative electrode graphite material prepared in Example 2 was mixed with stannous pyrophosphate, carbon black conductive agent and styrene-butadiene rubber binder in a mass ratio of 10:0.3:0.4:1.5 to form a powder mixture, and N-methylpyrrolidone was used as a solvent. The powder mixture and the solvent were mixed in a ratio of 1g:1mL, stirred into a slurry, and the slurry was coated on a copper foil current collector with a thickness of 10μm. The slurry coating thickness was 200μm, and dried and solidified to obtain a graphite negative electrode.

[0047] Example 6: This example prepares a graphite negative electrode, and the preparation steps are as follows.

[0048] The negative electrode graphite material prepared in Example 3 was mixed with stannous pyrophosphate, carbon black conductive agent and styrene-butadiene rubber binder in a mass ratio of 10:0.5:0.8:1.0 to form a powder mixture, and N-methylpyrrolidone was used as a solvent. The powder mixture and the solvent were mixed in a ratio of 1g:1mL, stirred into a slurry, and the slurry was coated on a copper foil current collector with a thickness of 10μm. The slurry coating thickness was 200μm, and dried and solidified to obtain a graphite negative electrode.

[0049] Comparative Example 1 This comparative example prepares a negative electrode graphite material. Compared with Example 1, this comparative example also uses maleic anhydride grafted polyethylene as the coating material, but it is not carbonized. The preparation steps of this comparative example are as follows.

[0050] Natural flake graphite is used as raw material and crushed.

[0051] The crushed graphite is spheroidized by graphite spheroidizing equipment to make the sphericity of the graphite reach 80%, and then screened to control the graphite particle size range of D10>5μm, D50=15±2μm, and D90<40μm.

[0052] Maleic anhydride grafted polyethylene is used as a coating material, and the coating material and spheroidized graphite particles are mixed in a mass ratio of 5:100; then the coating material is ground for 5 hours to make the coating material fully fine and evenly dispersed with the graphite particles; then the temperature is raised to 150°C to melt the maleic anhydride grafted polyethylene and coat the surface of the graphite particles; the coating is ground again to disperse the graphite particles coated with the coating material, and finally the coated graphite is demagnetized and sieved to obtain a negative electrode graphite material.

[0053] Comparative Example 2 This comparative example prepares a negative electrode graphite material. The only difference compared to Example 1 is that the maleic anhydride grafted polyethylene is replaced by polyethylene. This comparative example also carbonizes the polyethylene, and other conditions remain unchanged.

[0054] Comparative Example 3 In this comparative example, a negative electrode graphite material is prepared. Compared with Example 1, the difference is that the maleic anhydride grafted polyethylene is replaced with maleic anhydride grafted polypropylene, and the temperature at which the maleic anhydride grafted polypropylene is melted and coated on the surface of the graphite particles is changed to 200°C. In this comparative example, the maleic anhydride grafted polypropylene is also carbonized, and other conditions remain unchanged.

[0055] Comparative Example 4 In this comparative example, the negative electrode graphite material prepared in comparative example 1 is used to prepare a graphite negative electrode, and the preparation steps are the same as those in example 4, which are as follows.

[0056] Take comparative example 1 to prepare the negative electrode graphite material, and mix it with stannous pyrophosphate, carbon black conductive agent and styrene-butadiene rubber binder in a mass ratio of 10:0.4:0.6:1.2 to form a powder mixture, use N-methylpyrrolidone as solvent, and mix the powder mixture and the solvent in a ratio of 1g:1mL, stir to form a slurry, and coat the slurry on a copper foil current collector with a thickness of 10μm. The slurry coating thickness is 200μm, and dry and solidify to obtain a graphite negative electrode.

[0057] Comparative Example 5 In this comparative example, the negative electrode graphite material prepared in comparative example 2 is used to prepare a graphite negative electrode, and the preparation steps are the same as those in example 4, which are as follows.

[0058] Take comparative example 2 to prepare the negative electrode graphite material, and mix it with stannous pyrophosphate, carbon black conductive agent and styrene-butadiene rubber binder in a mass ratio of 10:0.4:0.6:1.2 to form a powder mixture, use N-methylpyrrolidone as solvent, and mix the powder mixture and the solvent in a ratio of 1g:1mL. Stir to form a slurry, and coat the slurry on a copper foil current collector with a thickness of 10μm. The slurry coating thickness is 200μm, and it is dried and cured to obtain a graphite negative electrode.

[0059] Comparative Example 6 In this comparative example, the negative electrode graphite material prepared in comparative example 3 is used to prepare a graphite negative electrode, and the preparation steps are the same as those in example 4, which are as follows.

[0060] Take comparative example 3 to prepare the negative electrode graphite material, and mix it with stannous pyrophosphate, carbon black conductive agent and styrene-butadiene rubber binder in a mass ratio of 10:0.4:0.6:1.2 to form a powder mixture, use N-methylpyrrolidone as solvent, and mix the powder mixture and the solvent in a ratio of 1g:1mL. Stir to form a slurry, and coat the slurry on a copper foil current collector with a thickness of 10μm. The slurry coating thickness is 200μm, and dry and solidify to obtain a graphite negative electrode.

[0061] Comparative Example 7 In this comparative example, the negative electrode graphite material prepared in Example 1 is used to prepare a graphite negative electrode. Compared with Example 4, the preparation steps thereof do not use stannous pyrophosphate. The preparation steps of this comparative example are as follows.

[0062] The negative electrode graphite material prepared in Example 1 was mixed with a carbon black conductive agent and a styrene-butadiene rubber binder in a mass ratio of 10:0.6:1.2 to form a powder mixture. N-methylpyrrolidone was used as a solvent, and the powder mixture and the solvent were mixed in a ratio of 1g:1mL. The mixture was stirred into a slurry, and the slurry was coated on a copper foil current collector with a thickness of 10μm. The slurry coating thickness was 200μm, and the graphite negative electrode was obtained by drying and curing.

[0063] Test Example 1 The particle size, tap density, specific surface area, and fixed carbon of the negative electrode graphite materials prepared in Example 1-3 and Comparative Example 1-3 were tested as follows: the particle size was tested by Malvern: Mastersizer 3000; the tap density was tested by BT-300; the specific surface area was tested by JW-DX dynamic nitrogen adsorption; and the fixed carbon was tested according to the provisions of GB / T3521-2008.

[0064] Electrochemical performance test (including first discharge specific capacity and first discharge efficiency): Any one of the graphite negative electrodes in Examples 4-6 and Comparative Examples 4-7 is used as the negative electrode. The metal lithium sheet is used as the positive electrode. The polypropylene porous membrane (celgard 2300) is used as the diaphragm. There are three electrolytes to test the compatibility of the negative electrode with the three electrolytes. The first electrolyte has a volume ratio of DMC:DEC:EC=1:1:1 as the solvent and a solute of 1 mol / L LiPF 6 , where DMC is dimethyl carbonate, DEC is diethyl carbonate, and EC is ethylene carbonate. The second electrolyte has a volume ratio of methanol and water = 1:1 as solvent, and the solute is 1 mol / L LiClO 4The third electrolyte has a volume ratio of methanol and water = 1:1 as solvent and a solute of 1 mol / L LiBF 4 Lithium-ion batteries with the same structure and dosage as above were assembled and tested using the Blue Power Battery Test System. The test range was 0.001-2.0V, and the charge and discharge were performed at a rate of 0.1C.

[0065] The compatibility of the negative electrode with the three electrolytes can refer to the test results of the K value. The K value indicates the penetration ability of the electrolyte into the material. The test method of the K value is as follows. The compatibility of the negative electrode graphite material with the lithium hexafluorophosphate electrolyte is evaluated by the penetration ability of the electrolyte into the negative electrode graphite material. The specific test method is as follows: Take a certain amount of any electrolyte configured in Test Example 1, and drip the electrolyte onto the negative electrode graphite material at a height of 5 mm vertically above the material. Read the time when the electrolyte is completely absorbed by the material (recorded as the penetration time t), calculate the trace area formed by the electrolyte when the material absorbs the electrolyte (recorded as the penetration area), and finally the calculation formula of the K value is:

[0066] Among them, K represents the penetration ability of the electrolyte into the material; V represents the volume of the electrolyte that penetrates into the material; t represents the penetration time of the electrolyte with volume V in the material; S represents the trace area formed on the surface of the material due to the penetration of the electrolyte V within the time t; ρ represents the compaction density of the material; l represents the thickness of the material after compaction.

[0067] The test results of the above test items are shown in Tables 1 to 3.

[0068] Table 1 Statistics of some properties of negative electrode graphite materials

[0069] Table 2 K value test statistics of negative electrode graphite materials

[0070] Table 3 Electrical performance test statistics

[0071] Table 2 shows that the K value of the negative electrode graphite materials of Examples 1-3 is 15.71-16.57 g / (cm 3 ·S), indicating that the negative electrode graphite material and the electrolyte have good compatibility. The K value of comparative example 1 is 11.39-12.20 g / (cm 3 ·S), indicating that the negative electrode graphite material of Comparative Example 1 has poor compatibility with the electrolyte. It can be seen that if the maleic anhydride grafted polyethylene is not carbonized, the compatibility of the negative electrode graphite material and the electrolyte will decrease. The K value of Comparative Example 2 is 12.72-13.38 g / (cm3 ·S), indicating that the negative electrode graphite material of Comparative Example 2 has poor compatibility with the electrolyte. It can be seen that replacing maleic anhydride grafted polyethylene with polyethylene reduces the compatibility of the negative electrode graphite material and the electrolyte. The K value of Comparative Example 3 is 14.15-14.43 g / (cm 3 ·S), indicating that the negative electrode graphite material of Comparative Example 3 has poor compatibility with the electrolyte. It can be seen that if maleic anhydride grafted polypropylene is used to replace maleic anhydride grafted polyethylene, the compatibility of the negative electrode graphite material and the electrolyte decreases.

[0072] Table 3 shows that Example 4-6 has a higher first discharge specific capacity and first discharge efficiency than Comparative Example 4-7, indicating that the graphite negative electrode prepared in Example 4-6 has more lithium storage space and higher lithium ion embedding efficiency in the negative electrode, which can also inhibit the growth of lithium dendrites. The raw material of Comparative Example 4 did not carbonize the maleic acid grafted polyethylene, and the conductivity and lithium storage space of the negative electrode were reduced, which reduced the first discharge specific capacity and first discharge efficiency of the battery. The graphite negative electrode prepared in Comparative Example 5 uses polyethylene instead of maleic anhydride grafted polyethylene for carbonization, and it has no grafted structure, and the conductivity and lithium storage space of the negative electrode are reduced, which reduces the first discharge specific capacity and first discharge efficiency of the battery. The graphite negative electrode prepared in Comparative Example 6 is carbonized by replacing maleic anhydride grafted polyethylene with maleic anhydride grafted polypropylene as raw material. The grafting rate of maleic anhydride grafted polypropylene is about 1.4%, and the grafting rate of maleic anhydride grafted polyethylene is about 8%. Maleic anhydride grafted polypropylene with a lower grafting rate leads to a decrease in the conductivity and lithium storage space of the negative electrode, which reduces the first discharge specific capacity and first discharge efficiency of the battery. Comparative Example 7 prepares the graphite negative electrode without adding stannous pyrophosphate. In addition to significantly reducing the lithium storage space and reducing the conductivity, it is also not conducive to the growth of a relatively complete SEI film, making the negative electrode not compatible with a variety of electrolytes, which reduces the first discharge specific capacity and first discharge efficiency of the battery.

[0073] The present application improves the compatibility of graphite with various electrolytes and the electrochemical properties of graphite materials by surface modification of natural graphite, and adds stannous pyrophosphate when preparing graphite negative electrodes, which has a certain protective effect on the negative electrode structure, enriches the number of negative electrode micropores, improves the wetting efficiency of the electrolyte on the negative electrode, and improves the capacity and discharge efficiency of the negative electrode, that is, further improves the compatibility of the graphite negative electrode with various electrolytes. The negative electrode graphite material and graphite negative electrode of the present application are suitable for use in high energy density lithium-ion batteries, and can improve the electrical performance of the battery.

[0074] The above are only some embodiments of the present application, and the protection scope of the present application is not limited to the above embodiments. For those skilled in the art, several improvements and extensions made according to the above embodiments without departing from the creativity of the present application should also fall within the protection scope of the present application.

Claims

1. A negative electrode graphite material, characterized in that: The negative electrode graphite material comprises core-shell particles in which a shell layer covers a core layer; the shell layer is carbonized maleic anhydride grafted polyethylene; and the core layer is graphite particles.

2. The negative electrode graphite material according to claim 1, characterized in that The mass ratio of the uncarbonized maleic anhydride grafted polyethylene and the graphite particles used to prepare the negative electrode graphite material is (2-10):

100.

3. The negative electrode graphite material according to claim 1, characterized in that The particle size distribution of the graphite particles is as follows: D10 is 5-13 μm, D50 is 13-17 μm, and D90 is 17-35 μm.

4. A method for producing a negative electrode graphite material according to any one of claims 1 to 3, characterized in that: The production method comprises: mixing and grinding maleic anhydride grafted polyethylene and graphite particles, heating to melt the maleic anhydride and coat the graphite particles, grinding again to disperse the graphite particles coated with the coating material, and then heating to 800-1500° C. and keeping the temperature for 5-20 hours in an oxygen-free atmosphere to obtain the negative electrode graphite material.

5. The method for producing negative electrode graphite material according to claim 4, characterized in that: The graphite particles are spheroidized graphite obtained by crushing and spheroidizing flake graphite as a raw material.

6. The method for producing the negative electrode graphite material according to claim 5, characterized in that: The sphericity of the spheroidized graphite is ≥80%.

7. A graphite negative electrode, characterized in that: The negative electrode graphite material comprises the negative electrode graphite material according to any one of claims 1 to 3, and further comprises stannous pyrophosphate, a conductive agent, a binder and a current collector; the negative electrode graphite material, the stannous pyrophosphate, the conductive agent and the binder are uniformly dispersed with each other in a mass ratio of 10: (0.3-0.5): (0.4-0.8): (1.0-1.5) and are solidified on the current collector.

8. A method for producing a graphite negative electrode as claimed in claim 7, characterized in that: The negative electrode graphite material, the stannous pyrophosphate, the conductive agent, the binder and the solvent are mixed into slurry, the slurry is coated on the current collector, and the slurry is dried and solidified to obtain the graphite negative electrode.

Citation Information

Patent Citations

  • Negative electrode active material and preparation method thereof, as well as lithium ion battery

    CN103367741A

  • Composite particle

    CN104471752A

  • Graphite composite material with functional coating layer, preparation method and application

    CN119092686A

  • Method for producing modified graphite

    CN1549362A

  • Modified graphite and its preparing method

    CN1581544A